Extraction, chemical modification by octenyl succinic and characterization of cyperus esculentus starch - Costa Neto,Jonas (2018)
Abstract The purpose of this study was to characterize, isolate and chemically modify tiger nut ( Cyperus sculentus L.) starch with octenyl succinic anhydride. The efficiency of the chemical modification was 0.04. Chemical composition, particle morphology (SEM), particle size, X-ray diffraction, infrared analysis, thermogravimetric analysis, differential scanning calorimetry and swelling and solubility power were determined for characterization of the native and modified starch. Both showed similar chemical composition and amylose and amylopectin contents, as well as absorption spectra in the infrared region without modification of the molecular structure and A-type crystalline pattern. The particles of both had an oval and spherical shape. The modified starch was more resistant to temperature and the gelatinization process occurred at 67.52 °C. These results suggest that tiger nut starch has a great industrial potential.